Shiʻr-i Iqbāl : Iqbāl ke shuʻūr-i taḵẖlīq kā jāʼizah - ʻĀbid, ʻĀbid ʻAlī, 1906-1971 (Bazm-i Iqbāl, 1977)
Critical appreciation of the creative genius of Sir Muhammad Iqbal, 1877-1938, eminent Urdu and Persian poet.